Information on the Prevalence and Extent of Alcohol Abuse Among Commercial Tricycle Operators in Calabar - Angioha, Pius U.; Akintola, Abayomi; Ogunnubi, Olusola; Butum, Bassey Eyong (Yayasan Ahmar Cendekia Indonesia, 2021)
This study examines the prevalence and extent of Alcohol abuse among commercial tricycle operators in Calabar, Cross River State, Nigeria. Adopting a descriptive quantitative research method, data was collected from 385 participants from 6424 registered tricycle operators in Calabar using a questionnaire. The participants were selected using the convenience and random sampling technique. Data collected from the field were subjected to descriptive statistics. Out of the 385 distributed instruments, 383 were returned and used for data analysis. From the analyzed data, the result revealed that all the participants, 100.00 per cent, have taken alcohol before. 81.46 per cent taken alcohol before while working, Majority of the tricycle drivers, 38.90 per cent believes that alcohol makes them have clearer vision when driving, 31.59 per cent argued that it makes them work longer, 10.97 per cent maintain that it is because they are used to alcohol. 12.27 per cent of the participants take alcohol at every opportunity they get, 18.02 per cent reported drinking every day. Result also revealed that all the tricycle riders have had accidents before, 77.81 per cent were under the influence of Alcohol when the accidents happened. Based on this result, the study concludes that there was a high prevalence of alcohol abuse among tricycle riders in Calabar. Hence there is a need for the enactment of proper laws that determines the legal limit of alcohol among drivers to checkmate the issue of driving under the influence and its attendant consequences.